2020
DOI: 10.47494/mesb.2020.4.40
|View full text |Cite
|
Sign up to set email alerts
|

Adults newly infected with hiv in burundi: a box-jenkins arima approach

Abstract: Using annual time series data on the number of adults (ages 15 and above) newly infected with HIV in Burundi from 1990 – 2018, the study predicts the annual number of adults who will be newly infected with HIV over the period 2019 – 2025. The study applied the Box-Jenkins ARIMA methodology. The diagnostic ADF tests as well as correlogram analysis show that the G series under consideration is an I (2) variable. Based on the AIC, the study presents the ARIMA (0, 2, 1) model as the optimal model. The residual cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The spatial-temporal risk cluster identified in Belém, in line with the evidence collected in Zimbabwe [38], may be associated with the success of strategies to combat the virus, such as the increased availability of rapid testing in Brazil between 2016 and 2017 [40]. Moreover, as a possible result of this success and as a corroboration of the findings of this study, Belém increased in the ranking among capital cities according to the composite index in the epidemiological bulletins of the disease in 2017, 2018, and 2019.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The spatial-temporal risk cluster identified in Belém, in line with the evidence collected in Zimbabwe [38], may be associated with the success of strategies to combat the virus, such as the increased availability of rapid testing in Brazil between 2016 and 2017 [40]. Moreover, as a possible result of this success and as a corroboration of the findings of this study, Belém increased in the ranking among capital cities according to the composite index in the epidemiological bulletins of the disease in 2017, 2018, and 2019.…”
Section: Discussionsupporting
confidence: 83%
“…On the contrary, in Zimbabwe, a study of time series ARIMA methods with HIV cases in people aged 15 years and older revealed an 'almost' constant mean over time, and after the expansion of access to treatment, new HIV infections are expected to decrease between 2019 and 2030, from approximately 31,321 to 20,071 new cases of HIV. The quality of this prediction showed very low measures of accuracy: On average, only 3.37% of the total number of new HIV infections are incorrect [38].…”
Section: Discussionmentioning
confidence: 99%